A Retrospective Study of State Aid Control in the German Broadband Market - Tomaso Duso; Mattia Nardotto; Jo Seldeslachts (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We provide an evaluation of the impact of public subsidy schemes that aimed to support the development of basic broadband infrastructure in rural areas of Germany. Such subsidies are subject to state aid control by the European Commission (EC). While the EC increasingly recognises the role of economic analysis in controlling public aid to companies, there are to date no full retrospective studies performed on state aid control, especially assessing the so-called balancing test. In this study, we do not only analyse whether the aid was effective in solving a market failure – low broadband coverage in rural areas – but also study its impact on competitive outcomes, on both rival firms and consumers. We adopt a difference-in-differences framework after using a matching procedure to account for selection on observables. We find that the aid significantly increased broadband coverage. More importantly, we find that the number of internet providers has significantly increased in the municipalities receiving aid. This additional entry decreased average prices. Therefore, the subsidies complied with EU state aid rules, both in terms of effectiveness and competition.
Keywords: C23; D22; L10; L40; L64; 330; state aid; ex-post evaluation; broadband; coverage; entry; competition; prices